Quantitative promoter methylation differentiates carcinoma ex pleomorphic adenoma from pleomorphic salivary adenoma - Schache, A G (Nature Publishing Group, 2010)
BACKGROUND: Potential epigenetic biomarkers for malignant transformation to carcinoma ex pleomorphic adenoma (Ca ex PSA) have been sought previously with and without specific comparison with the benign variant, pleomorphic salivary adenoma (PSA). Previous analysis has been limited by a non-quantitative approach. We sought to demonstrate quantitative promoter methylation across a panel of tumour suppressor genes (TSGs) in both Ca ex PSA and PSA. METHODS: Quantitative methylation-specific real-time polymerase chain reaction (qMSP) analysis of p16(INK4A), CYGB, RASSF1, RARβ, human telomerase reverse transcriptase (hTERT), Wilms’ tumour 1 (WT1) and TMEFF2 gene promoters was undertaken on bisulphite-converted DNA, previously extracted from archival fixed tissue specimens of 31 Ca ex PSA and an unrelated cohort of 28 PSA. All target regions examined had formerly been shown to be hypermethylated in salivary and/or mucosal head and neck malignancies. RESULTS: The qMSP demonstrated abnormal methylation of at least one target in 20 out of 31 (64.5%) Ca ex PSA and 2 out of 28 (7.1%) PSA samples (P<0.001). RASSF1 was the single gene promoter for which methylation is shown to be a statistically significant predictor of malignant disease (P<0.001) with a sensitivity of 51.6% and a specificity of 92.9%. RARβ, TMEFF2 and CYGB displayed no apparent methylation, while a combinatory epigenotype based on p16, hTERT, RASSF1 and WT1 was associated with a significantly higher chance of detecting malignancy in any positive sample (odds ratio: 24, 95% CI: 4.7–125, P<0.001). CONCLUSIONS: We demonstrate the successful application of qMSP to a large series of historical Ca ex PSA samples and report on a panel of TSGs with significant differences in their methylation profiles between benign and malignant variants of pleomorphic salivary adenoma. qMSP analysis could be developed as a useful clinical tool to differentiate between Ca ex PSA and its benign precursor.